2017
DOI: 10.1002/cphc.201701030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Long‐Range Electronic Effect of a Fluorous Ponytail on Metal Coordination during Solvent Extraction

Abstract: With the need for a precise description of the long-range electronic effects of a perfloroalkyl chain (F-ponytail) grafted onto metal chelators, we studied in detail the effect of a spacer inserted between the polar complexing head and the F-ponytail, in relation to the metal coordination ability of the resulting molecules. The prepared molecules were then applied for the extraction of various metals from an aqueous phase into an organic phase, and the optimum spacer length could be estimated to be between thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Besides, in classical solvent extraction, studies between malonamides and fluorinated malonamides demonstrated their analogous complexation of metals. 64 Shimizu et al 31 proposed a chemical coordination for lanthanide oxides using a TBP− HNO 3 −H 2 O system, in which three nitrate anions are used for charge neutralization but the number of TBP molecules used varies. In this study, we utilized a molar ratio of 3.5 for the La 3+ /TFP extraction.…”
Section: Solid Scco 2 Extraction the Extraction Efficiency Is Defined Asmentioning
confidence: 99%
“…Besides, in classical solvent extraction, studies between malonamides and fluorinated malonamides demonstrated their analogous complexation of metals. 64 Shimizu et al 31 proposed a chemical coordination for lanthanide oxides using a TBP− HNO 3 −H 2 O system, in which three nitrate anions are used for charge neutralization but the number of TBP molecules used varies. In this study, we utilized a molar ratio of 3.5 for the La 3+ /TFP extraction.…”
Section: Solid Scco 2 Extraction the Extraction Efficiency Is Defined Asmentioning
confidence: 99%
“…During our previous work, the fundamental studies performed along with the process development studies revealed that the initial design of the chosen diamide, N,N'-dimethyl-N,N'dibutylteradecylmalonamide (DBMA, Figure 1), was not optimized for selective Pd(II) extraction. 26,[28][29][30] DBMA was selected as this molecule is the former lanthanide/actinide separation molecule, so that it was readily available from French CEA. However, its molecular design has been performed targeting high distribution ratios for lanthanides(III) cations, [31][32][33] and its ability to also extract palladium(II) was instead a side-effect.…”
Section: Introductionmentioning
confidence: 99%